2015
DOI: 10.1021/bi501534x
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Stabilities and Sequence-Dependent Base Pair Opening Dynamics of Watson–Crick Base Pairs with 5-Hydroxymethylcytosine, 5-Formylcytosine, or 5-Carboxylcytosine

Abstract: 5-Hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC) form during active demethylation of 5-methylcytosine (5mC) and are implicated in epigenetic regulation of the genome. They are differentially processed by thymine DNA glycosylase (TDG), an enzyme involved in active demethylation of 5mC. Three modified Dickerson–Drew dodecamer (DDD) sequences, amenable to crystallographic and spectroscopic analyses and containing the 5′-CG-3′ sequence associated with genomic cytosine methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(132 citation statements)
references
References 102 publications
11
121
0
Order By: Relevance
“…The overall reaction involves the enzyme binding to DNA, followed by bending and inserting an amino acid residue via the minor groove to help flip out the desired base, exposing the glycosyl bond for cleavage within the TDG active site. Such a structure in the absence of enzyme would be at a much higher energy than the relaxed B-DNA, and our data and those of Szulik et al 19 indicate that the population of flipped out bases is very low in free f C-DNA. To achieve a productive complex, the flipped-out base must make a large number of interactions with the enzyme to compensate for the local energy of distortion of the duplex.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The overall reaction involves the enzyme binding to DNA, followed by bending and inserting an amino acid residue via the minor groove to help flip out the desired base, exposing the glycosyl bond for cleavage within the TDG active site. Such a structure in the absence of enzyme would be at a much higher energy than the relaxed B-DNA, and our data and those of Szulik et al 19 indicate that the population of flipped out bases is very low in free f C-DNA. To achieve a productive complex, the flipped-out base must make a large number of interactions with the enzyme to compensate for the local energy of distortion of the duplex.…”
Section: Discussionsupporting
confidence: 80%
“…This similarity is also the case for f C in RNA which is also A-form, 37 and in a modified Dickerson-Drew dodecamer containing f C which is B-form in the crystal state. 19,21 Furthermore, our NMR data show that in solution these duplexes all adopt the B conformation, and that the differences induced by the f C modification are rather small and local, and unlikely to act as a gross structural recognition feature for TET, 38 TDG 39 or other enzymes. We conclude that there is no compelling evidence for a unique f C-dependent F-DNA structure, nor are the specific hydration patterns in the X-ray structure likely to be relevant for B-form duplexes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On average, the confal score improved by 7 after application of the PDB_REDO protocol, but the fraction of reassigned NtC classes varied widely between 0 and 77% in individual structures. The confal values showed significant improvement, for example, in the structure with PDB entry 1d29 (Larsen et al, 1991), while no changes were observed in PDB entry 4i9v (Szulik et al, 2015) and a mixture of increased and lowered confal values were found in PDB entry 5bna (Wing et al, 1984) (Supplementary Table S3). Overall, the PDB_REDO protocol improves the deposited coordinates somewhat, but better molecular templates provided by the NtC classes can constrain the re-refinement more effectively.…”
Section: B-a: Conformers Bridging B-form To A-formmentioning
confidence: 99%
“…Furthermore, the structurally related E. coli mismatch uracil glycosylase (eMUG) can excise 5caC and 5fC as well (74,82). Both 5fC and 5caC exhibit an intrabase hydrogen bond between their formyl or carboxyl oxygen atoms, respectively, and the adjacent cytosine N 4 exocyclic amine nitrogen atom, both in the free form (83) and in the protein-bound form (58) (Fig. 3, h and i, top panels).…”
Section: Active Dna Demethylation Via Base Excisionmentioning
confidence: 99%